2013
DOI: 10.1007/s10935-013-0321-4
|View full text |Cite
|
Sign up to set email alerts
|

Using Effort-Reward Imbalance Theory to Understand High Rates of Depression and Anxiety Among Clergy

Abstract: The clergy occupation is unique in its combination of role strains and higher calling, putting clergy mental health at risk. We surveyed all United Methodist clergy in North Carolina, and 95% (n = 1,726) responded, with 38% responding via phone interview. We compared clergy phone interview depression rates, assessed using the Patient Health Questionnaire (PHQ-9), to those of in-person interviews in a representative United States sample that also used the PHQ-9. The clergy depression prevalence was 8.7%, signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
75
3
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(85 citation statements)
references
References 53 publications
6
75
3
1
Order By: Relevance
“…However, studies show a higher prevalence of depression among clergy compared with the general populations (Knox et al 2002(Knox et al , 2005(Knox et al , 2007Proulx 2008). Although several of these studies had small, nonrandom samples, Proeschold-Bell et al (2013) also found a higher depression rate among a representative sample of all United Methodist clergies in North Carolina compared with a general population.…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…However, studies show a higher prevalence of depression among clergy compared with the general populations (Knox et al 2002(Knox et al , 2005(Knox et al , 2007Proulx 2008). Although several of these studies had small, nonrandom samples, Proeschold-Bell et al (2013) also found a higher depression rate among a representative sample of all United Methodist clergies in North Carolina compared with a general population.…”
Section: Introductionmentioning
confidence: 95%
“…For example, Knox et al (2002) and Proeschold-Bell et al (2013) found a higher incidence of anxiety symptoms among clergy compared with the general population. However, in a UK study of Anglican clergy, male clergy had more anxiety than men in the general population, while female clergy had less anxiety than women in the general population.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To better understand what may be contributing to these high rates of mental illness symptoms, Proeschold-Bell and her colleagues examined the predictors of depression and anxiety, choosing constructs based on the popular occupational health theory of Effort-Reward Imbalance Theory. As expected, rewards of ministry such as ministry satisfaction and lower financial stress related to less depression and anxiety, whereas work efforts such as greater job stress and life unpredictability related to more depression and anxiety (Proeschold-Bell, Miles, Toth et al, 2013).…”
Section: The Duke Clergy Health Initiativementioning
confidence: 64%
“…In the 2008 survey, they interviewed one-third of the clergy participants by phone, in order to account for mode effects when comparing clergy data with those from other studies that used phone or inperson data collection. They found that 8.7% of clergy interviewed by phone qualified for moderate or higher depression based on a depression screener (the PHQ-9), compared to only 5.5% of a representative sample of people from the United States, who were interviewed inperson using the same depression screener (Proeschold-Bell, Miles, Toth et al, 2013). The CHI also found that 11.1% of clergy who took the survey items in a self-administered web or paper format qualified for depression, and that 13.5% qualified for anxiety using the Hospital Anxiety and Depression Scale (unfortunately, there was not a good national comparison study that used the same anxiety measure).…”
Section: The Duke Clergy Health Initiativementioning
confidence: 99%